Indirect sinus lift done using "Autogenous Core Lift" Technique in combination with alloplastic phosphosilicate putty in atrophic maxillary posterior region: A clinical report with 1-Year follow-up - Umesh Y Pai; Shobha Rodrigues; Puneeth Hegde; Nikita Khurana (Wolters Kluwer Medknow Publications, 2017)
Pneumatization of the sinus is a common occurrence after extraction of maxillary posterior teeth. Implant procedures require a clinically acceptable level of bone to be present for implants to be placed in function. Residual bone with >4 mm of height can be managed using the indirect sinus lift procedure, whereas bone height <4 mm requires a direct sinus lift using lateral window approach. This clinical case report describes the use of autogenous core used to lift the membrane in conjunction with calcium phosphosilicate putty using minimal armamentarium, thereby avoiding the associated morbidity and complications associated with a direct sinus lift procedure.